THE PROBLEMS OF THAI STUDENTS IN MASTERING ENGLISH SPEAKING SKILLS IN THE ISLAMIC UNIVERSITY OF LAMONGAN - Tahe, Aleeya (Universitas Islam Lamongan, 2020)
English speaking skills are very important to communicate in the world. Most of the people communicate with other people by using speaking skills. The difficult skill to master in learning English for Thai students is speaking skills, especially those who are learning English in Indonesia speaking skill seems to be the most difficult one to learn. Whereas, it is the most important skill that leads to effective communication between people. Speaking skill is considered as the most important means of communication. Although students still have problems with their English speaking skills. Thai students who study at the English department academic still get problems in speaking skills and it needs overcoming with their English problems. The main objective of this study is to know the problems of Thai students in mastering English speaking skills in the Islamic university of Lamongan (Indonesia).Â Â Keywords: Thai Student, English speaking skill